Structurally different mixed linkage β-glucan supplements differentially increase secondary bile acid excretion in hypercholesterolaemic rat faeces. Issue 1 (13th December 2019) - Iaccarino, Nunzia; Khakimov, Bekzod; Mikkelsen, Mette Skau; Nielsen, Tina Skau; Jensen, Morten Georg; Randazzo, Antonio; Engelsen, Søren Balling
Abstract : This study demonstrates that structurally different barley β-glucans promote the primary and secondary bile acids' excretion in a selective manner depending on β-glucans molecular structure. Abstract : Mixed linkage (1→3), (1→4)-β-d -glucan (BG) is a soluble fibre available from oat and barley grains that has been gaining interest due to its health-promoting role in cardiovascular diseases and its ability to modulate the glycaemic index which is beneficial for people with diabetes. This study investigates the effect of three purified barley BGs, with different molecular weight and block structure, on faecal bile acid excretion in hypercholesterolaemic rats. Wistar rats (48 male) were divided in four groups: Control group fed with the cellulose-rich diet (CON); Glucagel group fed with the commercial BG (GLU, 100 kDa), and rats fed with low molecular weight BG (LBG, 150 kDa) and medium molecular weight BG (MBG, 530 kDa). The bile acid profiles of rat faecal samples were measured using gas chromatography-mass spectrometry (GC-MS). A metabolite profiling approach led to the identification of 7 bile acids and 45 other compounds such as sterols, fatty acids and fatty alcohols. Subsequent application of ANOVA-simultaneous component analysis and Principal Component Analysis revealed that all three BG diets increased bile acid faecal excretion compared to the control group. The bile acid excretion was found to be different in all three BG diets and the MBG group showed a significantly higher level of faecal secondary bile acids, including deoxycholic acid, hyodeoxycholic acid, and lithocholic acid. We hypothesise that the hydrophobic surface of the secondary bile acids, which are known to cause colon cancer, has high affinity to the hydrophobic surfaces of cellulosic blocks of the BG. This in vivo study demonstrates that the molecular weight and/or block structures of BG modulate the excretion of secondary bile acids. This finding suggests that developing diets with designed BGs with an optimal molecular structure to trap carcinogenic bile acids can have a significant impact on counteracting cancer and other lifestyle associated diseases.